Immune checkpoints in hematologic malignancies: What made the immune cells and clinicians exhausted!. Issue 12 (7th May 2020) - Hajifathali, Abbas; Parkhideh, Sayeh; Kazemi, Mohammad H.; Chegeni, Rouzbeh; Roshandel, Elham; Gholizadeh, Majid
Abstract: Hematologic malignancies comprise a considerable part of cancers with high mortality at any age. Since the introduction of hematopoietic stem cell transplantation (HSCT), the overall survival of patients dramatically increased. The main goal of HSCT is the induction of a graft‐versus‐leukemia effect to eradicate the residual cancer cells and also reconstitute a healthy immune system for patients. However, relapse is a nettlesome challenge of HSCT. Like many other tumors, hematologic cancer cells induce immune exhaustion leading to immune escape and relapses after HSCT. Besides malignant cells, inhibitory cells such as tumor‐associated macrophages and myeloid‐derived suppressor cells express various inhibitory receptors capable of inducing exhaustion in immune cells, especially T and natural killer cells. The significance of immune checkpoint blocking in tumor regression in clinical trials led to the 2018 Nobel Prize in Physiology/Medicine. Here, we reviewed the clinical roles of immune checkpoints in hematologic malignancies and post‐HSCT relapses. Abstract : Despite the beneficial roles of hematopoietic stem cell transplantation (HSCT) in hematologic malignancies, relapse is still a nettlesome challenge. Hematologic cancer cells induce exhaustion in immune cells through several mechanisms, such as inhibitory immune checkpoints, which lead to immune escape and relapses after HSCT. We reviewed the clinical roles of immune checkpoints in hematologic malignancies and post‐HSCT relapses.